DNA-PKcs inhibition impairs HDAC6-mediated HSP90 chaperone function on Aurora A and enhances HDACs inhibitor-induced cell killing by increasing mitotic aberrant spindle assembly. Issue 2 (17th January 2021) - Yu, Lan; Lang, Yue; Guo, Jiaming; Cai, Jianming; Shang, Zeng-Fu; Chen, Benjamin P.C
ABSTRACT: Combining targeted therapeutic agents is an attractive cancer treatment strategy associated with high efficacy and low toxicity. DNA-dependent protein kinase catalytic subunit (DNA-PKcs) is an essential factor in DNA damage repair. Studies from us and others have revealed that DNA-PKcs also plays an important role in normal mitosis progression. Histone deacetylase (HDACs) inhibitors commonly lead to mitotic aberration and have been approved for treating various cancers in the clinic. We showed that DNA-PKcs depletion or kinase activity inhibition increases cancer cells' sensitivity to HDACs inhibitors in vitro and in vivo . DNA-PKcs deficiency significantly enhances HDACs inhibitors (HDACi)-induced mitotic arrest and is followed by apoptotic cell death. Mechanistically, we found that DNA-PKcs binds to HDAC6 and facilitates its acetylase activity. HDACi is more likely to impair HDAC6-induced deacetylation of HSP90 and abrogate HSP90's chaperone function on Aurora A, a critical mitotic kinase that regulates centrosome separation and mitotic spindle assembly in DNA-PKcs-deficient cells. Our current work indicates crosstalk between DNA-PKcs and HDACs signaling pathways, and highlights that the combined targeting of DNA-PKcs and HDACs can be used in cancer therapy. Abbreviations: DNA-PKcs, DNA-dependent protein kinase catalytic subunit, HDACs, Histone deacetylases, DSBs, DNA double-strand breaks, ATM, ataxia telangiectasia mutated, ATR, ATM-Rad3-related